1985
DOI: 10.1111/j.1399-3054.1985.tb02382.x
|View full text |Cite
|
Sign up to set email alerts
|

The site of 1‐aminocyclopropane‐1‐carboxylic acid synthesis in senescing carnation petals

Abstract: Spiegelstein, H, and Mayak, S. 1985, The site of 1-amitiocy-cIopropane-1-carbosylic acid syntbesis in senescing carnation petals, -Physiol, Plant. 65;[196][197][198][199][200][201][202] To study the cause of the uneven production of ethyiene by upper and basal portions of detached petals of carnation (Dianthus caryophyllus L, cv. White Sim), the petals were divided and exposed to ethylene (30 (il 1^' for 16 h). The treatment induced rapid wilting and autocatalytic ethylene production in the basai portion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…It may therefore be concluded that the transported signal is not ACC but, rather, ethylene itself may be translocated or the lip may become more sensitive to ethylene following emasculation. The latter would meet our expectations as the existence of (mobile) ethylene-sensitivity factor(s) has also been suggested in cyclamen, petunia, and carnation flowers (7,9,13,19).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It may therefore be concluded that the transported signal is not ACC but, rather, ethylene itself may be translocated or the lip may become more sensitive to ethylene following emasculation. The latter would meet our expectations as the existence of (mobile) ethylene-sensitivity factor(s) has also been suggested in cyclamen, petunia, and carnation flowers (7,9,13,19).…”
Section: Discussionsupporting
confidence: 61%
“…In Cyclamen flowers, pollination-induced corolla abscission was ascribed to the action of a pollination-induced ethylene-sensitivity factor as abscission in pollinated flowers could be prevented by silver thiosulphate whereas it could not be induced by ethylene or ACC in nonpollinated flowers (7). Similarly, such a mobile ethylene-sensitivity factor was suggested to be produced in the lower portion of the carnation petal (13).…”
mentioning
confidence: 99%
“…We have demonstrated interorgan transport of ACC, as has been previously reported in other systems (3,5,6,9,12,18,21,23,28,29). In shoots, ACC is converted to ethylene, which in turn causes leaf abscission.…”
Section: Water Stress and Leaf Abscission In Citrussupporting
confidence: 53%
“…Xylem transport of ACC from roots to shoots was first demonstrated by Bradford and Yang to induce epinasty in tomato plants subjected to anaerobic root stress (5, 6). Later, interorgan ACC transport was shown in several systems (3,9,12,18,21,23,28,29). However, no studies to test the relationship between water stress-induced abscission and xylem transport of ACC have been made.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one can speculate that either another ACC synthase gene is leading to the ethylene responsible for this effect or that the sensitivity of the tissue to ethylene is enhanced (GuzmBn and Ecker, 1990). In addition, the possible interorgan transport of ACC to target tissues cannot be excluded because this phenomenon has been demonstrated in various cases (Amrhein et al, 1982;Fuhrer and Fuhrer-Fries, 1985; Mor et al, 1985; Nichols and Frost, 1985; Kiss and Koning, 1989;Woltering, 1990;Tudela and Primo-Millo, 1992;ONeill et al, 1993).…”
Section: Expression Pattern Of Acsl Changes During Growth In the Darkmentioning
confidence: 99%